Leading culture change in global organizations : aligning culture and strategy - Denison, Daniel R. (San Francisco : Jossey-Bass, 2012)
'Filled with case studies from firms such as GT Automotive, GE Healthcare China, Vale, Dominos, Swiss Re Americas Division, and Polar Bank, among others, this book (written by Dan Denison and his co-authors) combines twenty years of research and survey results to illustrate a critical set of cultural dynamics that firms need to manage in order to remain competitive. Each chapter uses a case as a means to illustrate an important aspect of culture change focusing on seven common culture-change dilemmas including creating a strategic alignment, keeping strategy simple, and more'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Organizational behavior -- Case studies; Organizational change -- Case studies; Corporate culture -- Case studies; International business enterprises -- Case studies